Pengaruh Performance Expectancy Terhadap Minat Implementasi Sistem Pengelolaan Keuangan Daerah (SIPKD) di Pemkot Padang - Anisa, Feby; Ananda, Febryandhie (LLDIKTI Wilayah X, 2019)
The purpose of this study is to examine the effect of performance expectancy on the interest in implementing a regional financial management information system (SIPKD). This research is based on the results of a test of 80 respondents using information systems of regional financial managers who work in the government of Padang City Hall. This study uses a research respondent that is distributed directly and uses a simple linear regression technique to test the research data with the help of SPSS 25. This study uses an independent variable performance expectancy and one dependent variable, namely: interest in implementing regional financial management information systems. The results of the study show that partially, performance expectancy has a significant effect on the interest in implementing the regional financial management information system